2012
DOI: 10.1371/journal.pone.0045762
|View full text |Cite
|
Sign up to set email alerts
|

Non-Structured Amino-Acid Impact on GH11 Differs from GH10 Xylanase

Abstract: The Aspergillus niger xylanase (Xyn) was used as a model to investigate impacts of un-structured residues on GH11 family enzyme, because the β-jelly roll structure has five residues (Ser1Ala2Gly3Ile4Asn5) at N-terminus and two residues (Ser183Ser184) at C-terminus that do not form to helix or strand. The N- or/and C-terminal residues were respectively deleted to construct three mutants. The optimal temperatures of XynΔN, XynΔC, and XynΔNC were 46, 50, and 46°C, and the thermostabilities were 15.7, 73.9, 15.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Usually thermophilic GH11 xylanases possess a β-strand in the N-terminal region, while mesophilic GH11 xylanases have a long irregular loop at the same position [30]. It is more likely that the reason PjxA was unstable at elevated temperature is the looseness of the irregular loop.…”
Section: Discussionmentioning
confidence: 99%
“…Usually thermophilic GH11 xylanases possess a β-strand in the N-terminal region, while mesophilic GH11 xylanases have a long irregular loop at the same position [30]. It is more likely that the reason PjxA was unstable at elevated temperature is the looseness of the irregular loop.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that terminal amino acid residues are crucial for the entire enzyme (42,54). Liu et al have reported that disordered terminal amino acid deletions increased regular secondary structural contents, which led to slow decreases in Gibbs free energy in the thermal denaturation process and ultimately enhanced enzyme thermostability (55).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, terminal sequences also influence enzymes in different ways (23). For example, the C-terminal region of Trichoderma reesei endo-1,4-xylanase changed its half-life (24), deletion of the N-and C-terminal sequences of Aspergillus niger xylanase resulted in a lower temperature optimum and decreased thermostability (25), and disruption of the terminal interaction of a GH10 xylanase resulted in decreased stability (26). The reason might be that removal of these terminal sequences changed the secondary structure contents, aromatic cluster formation, in vivo folding, and Gibbs free energy.…”
Section: Discussionmentioning
confidence: 99%